Vanishing ice : glaciers, ice sheets, and rising seas - Gornitz, Vivien (Columbia University Press, 2019)
"The Arctic is thawing. Vanishing Ice is a powerful depiction of the dramatic transformation of the cryosphere--the world of ice and snow--and its consequences for the human world. Delving into the major components of the cryosphere, including ice sheets, valley glaciers, permafrost, and floating ice, Vivien Gornitz gives an up-to-date explanation of key current trends in the decline of ice mass. Drawing on a long-term perspective gained by examining changes in the cryosphere and corresponding variations in sea level over millions of years, she demonstrates the link between thawing ice and sea-level rise to point to the social and economic challenges on the horizon. Gornitz highlights the widespread repercussions of ice loss, which will affect countless people far removed from frozen regions, to demonstrate why the big meltdown matters to us all"--